Downside financial risk is misunderstood - Philip W. S. Newall (Judgment and Decision Making, 2016)
The mathematics of downside financial risk can be difficult to understand: For example a 50% loss requires a subsequent 100% gain to break-even. A given percentage loss always requires a greater percentage gain to break-even. Instead, many non-expert investors may assume for example that a 50% gain is sufficient to offset a 50% loss. Over 3,498 participants and five experiments, the widespread illusion that a sequence of equal percentage gains and losses produces a zero overall return was demonstrated. Participants continued to err frequently, even with percentage returns of +/-100%, or when financially incentivized. Financial literacy, numeracy, and deliberation were all shown to independently contribute to accurate performance. These results have implications for promoting the understanding of downside financial risk.